FIRST LANGUAGE VOCABULARY DEVELOPMENT AND PHONOLOGICAL DEVELOPMENT OF AN INDONESIAN CHILD: A CASE STUDY - Sugiyanta (Dialectical Literature and Educational Journal, 2021)
First language vocabulary development and phonological development are important for a child to interact with others and to acquire second language. This current research aims to explore the first language vocabulary development and phonological development of an Indonesian child. The subject of this current research is an Indonesian female child aged 2.10 years. Recordings were employed as the research instrument to collect data. The data were collected by recording the child’s utterances within a three-month period, commencing from February 5, 2019 to April 23, 2019. There were nine (9) recordings in February, twenty-five (25) recordings in March, and twenty-six (26) recording in April. To explore the child’s first language vocabulary and phonological development, the recordings of the child’s utterances were transcribed. The findings show that the vocabulary development of the child occurred in the names of animals, vegetables, fruits, transportation, stationary, numbers, colours, and family members. In addition, the findings also indicate that child’s phonological development did not yet happen in the second month of the research (March 2019). It occurred in the third month only in the categories of other things and colours. A study should be further conducted with more categories, not only focusing on the main four parts of speech – nouns, verbs, adjectives, and adverbs, but also on pronouns, prepositions, conjunctions, and articles.